Mitral valve thrombosis in term pregnancy: A case report and review of the literature - Andrea Espiau Romera; Javier Jimeno Sánchez; Javier Navarro Sierra; Teresa Simón Paracuellos; Francisco Javier Villalobos Salguero; Belén Rodríguez Solanilla (Elsevier, 2021)
Objective: With this case report would like to emphasize the complexity that involves the management of pregnant women with mechanical heart valves. In that sense, an adequate interdisciplinary management of this potentially serious pathology is required for maternal and fetal well-being. Case report: A 32-year-old primipara, with a mechanical mitral valve replacement, was admitted to our emergency department at 37+1 weeks of gestation with acute dyspnea and presyncope. The patient was diagnosed with mechanical mitral valve thrombosis and, due to the appearance of hemodynamic instability, the patient underwent an uncomplicated emergency caesarean section and subsequent prosthetic mitral valve replacement. The patient was discharged six days after surgery, without any obstetric complication and with normal valve function. Conclusion: This case report shows that, despite strict control and optimal anticoagulation regimen, pregnant women with mechanical heart valves still have a high risk of developing valve thrombosis.